2017
DOI: 10.1111/exd.13228
|View full text |Cite
|
Sign up to set email alerts
|

IL‐36γ has proinflammatory effects on human endothelial cells

Abstract: Interleukin-36 cytokines are predominantly expressed by epithelial cells. Significant upregulation of epidermal IL-36 is now a recognised characteristic of psoriatic skin inflammation. IL-36 is known to induce inflammatory responses in dendritic cells, fibroblasts and epithelial cells. Although vascular alterations are a hallmark of psoriatic lesions and dermal endothelial cells are well known to play a critical role in skin inflammation, the effects of IL-36 on endothelial cells are unexplored. We here show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…Therefore, exosomes probably play an immunomodulatory role in the CC microenvironment. The pro‐inflammatory cytokine, IL‐36γ, has the ability to induce inflammation in keratinocytes via the Wingless/integrase 1 signaling pathway . Rana and colleagues demonstrated the presence of IL‐36γ inside exosomes derived from polyinosinic:polycytidylic acid (poly(I:C))‐treated keratinocytes.…”
Section: The Relationship Between Exosomes Inflammation and Cervicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, exosomes probably play an immunomodulatory role in the CC microenvironment. The pro‐inflammatory cytokine, IL‐36γ, has the ability to induce inflammation in keratinocytes via the Wingless/integrase 1 signaling pathway . Rana and colleagues demonstrated the presence of IL‐36γ inside exosomes derived from polyinosinic:polycytidylic acid (poly(I:C))‐treated keratinocytes.…”
Section: The Relationship Between Exosomes Inflammation and Cervicalmentioning
confidence: 99%
“…The pro-inflammatory cytokine, IL-36γ, has the ability to induce inflammation in keratinocytes via the Wingless/integrase 1 signaling pathway. 136,137 Rana and colleagues demonstrated the presence of IL-36γ inside exosomes derived from polyinosinic:polycytidylic acid (poly(I:C))-treated keratinocytes. Previous studies have shown that HPV-16 inhibited the poly(I:C)-stimulated expression of some proinflammatory genes.…”
Section: The Relationship Between Exosomes Inflammation and Cervicalmentioning
confidence: 99%
“…3,4 The IL-36 cytokines (IL-36a, IL-36b, IL-36c and IL-36RA) are interleukins of the IL-1 cytokine family and are mainly produced by keratinocytes. 5 The three different agonistic isoforms of IL-36 (IL-36a, IL-36b, IL-36c) are proinflammatory and are induced by themselves 6,7 as well as by other cytokines, such as IFN-c, IL-1a, IL-1b, IL-17, IL-22, IL-23 and TNFa. 5,[8][9][10] IL-36a, IL-36b and IL-36c have similar functions.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines are members of the wider IL‐36 family and are associated with the psoriatic skin inflammation . IL‐36 has inflammatory effects on a range of cells including stroma, T‐cells, fibroblast, and myeloid cells . The inflammatory effect of IL‐36 cytokines is blocked by the naturally occurring IL‐36 antagonist (IL‐36Ra) .…”
Section: The Concept Of Il‐23–independent Il‐17 Productionmentioning
confidence: 99%
“…155 IL-36 has inflammatory effects on a range of cells including stroma, T-cells, fibroblast, and myeloid cells. 156,157 The inflammatory effect of IL-36 cytokines is blocked by the naturally occurring IL-36 antagonist (IL-36Ra). 156 The importance of IL-36 in psoriatic skin inflammation gained greater attention with the discovery that a loss of function in the IL-36Ra is associated with generalized pustular psoriasis (GPP) psoriasis (generalized pustular psoriasis).…”
Section: Role Of Il-36 At the Enthesismentioning
confidence: 99%